A thermistor material based on high entropy concept and preparation method thereof

The high-entropy oxide material (Co0.2Cr0.2Fe0.2Mg0.2Zn0.2) 3O4 designed through the high-entropy concept has solved the problem of degradation in the stability of traditional thermosensitive ceramic materials, and achieved the need for high-precision temperature measurement in the range of 0℃ to 100℃.

CN117038240BActive Publication Date: 2025-04-04YANCHUANG PHOTOELECTRIC TECH GANZHOU
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311131862.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-04-04
Estimated Expiration
2043-09-04

AI Technical Summary

Technical Problem

During the use of traditional thermosensitive ceramic materials or under thermal stress, the slight ion migration of cations in the octahedral structure leads to a decrease in material stability, affecting high-precision temperature measurement.

Method used

The new high-entropy oxide material (Co0.2Cr0.2Fe0.2Mg0.2Zn0.2) 3O4 is designed using the concept of high-entropy. The structural stability of the material is improved through the composition design idea of ​​"high-entropy alloy", and the material is prepared by the preparation method of transition metal oxide thermosensitive ceramics.

Benefits of technology

In the temperature range of 0°C to 100°C, the material exhibits obvious negative temperature coefficient characteristics, with an entropy value of 2.08R, and the material constant and resistivity are within the appropriate range, which significantly improves the structural stability and measurement accuracy of the thermosensitive ceramic material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117038240B_ABST
    Figure CN117038240B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of temperature measurement technology, and relates to a new type of thermistor material in thermistors. Specifically, a thermistor material based on the concept of high entropy and a preparation method thereof are provided to improve the structural stability of thermistor ceramic materials. The present invention applies the composition design concept of "high entropy alloy" to the thermistor material to obtain the thermistor material: (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4, where the special electronic structure of Mg and Zn atoms makes the thermistor material have an obvious negative temperature coefficient characteristic in the temperature range of 0℃~100℃, and the entropy value of the material reaches 2.08R, and the material constant is B 25℃ / 50℃ =4213K~4837K, temperature 25℃, resistivity is 4.23×10 5 Ω.cm~5.45×10 5 Ω.cm, which is very suitable as a sensitive body of a thermistor. In addition, the thermistor material is prepared by a preparation method of a transition metal oxide thermistor ceramic, the preparation process is simple, and the prepared thermistor material has stable performance and good consistency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of temperature measurement, relates to a new type of thermistor material in a thermistor, and specifically provides a thermistor material based on a high entropy concept and a preparation method thereof. Background Art

[0002] Negative Temperature Coefficient (NTC) thermistors are a type of electronic component whose resistance decreases exponentially with increasing temperature. They are widely used in temperature measurement in various fields due to their advantages such as high sensitivity, fast response speed, and good stability. The resistance value of thermistors usually drifts slightly during use, resulting in a decrease in measurement accuracy during high-precision temperature measurement. This is closely related to the stability of the core sensitive body (thermal ceramic material) of thermistors. At present, manganese-containing multi-element negative temperature coefficient (NTC) thermistor materials are the most widely used; however, during use or under the action of thermal stress, the cations in the traditional spinel structure will undergo slight ion migration in the octahedral structure, causing the cations to be in a metastable state, thereby affecting the stability of the thermistor; therefore, there is an urgent need to develop a new type of thermistor material with stable structure.

[0003] In recent years, the performance advantages brought by "high entropy" have set off a wave of research on high entropy ceramics in the scientific community. The design concept is mainly to increase the mixing entropy of the material by increasing the number of components, so that the entropy value of the material system reaches above 1.61R and a stable solid solution is obtained. For example, the spinel structured high entropy oxide (Co, Cr, Fe, Mn, Ni)3O4 used in lithium-ion batteries has obtained a high capacity (discharge / charge, 1034 / 680mAh g -1 ) and excellent cycle performance, which is attributed to Li + The stabilizing effect of entropy in the intercalation / de-intercalation process; however, the manganese and nickel elements are easy to change valence, which is still not conducive to the structural stability of the material. On this basis, the present invention creatively synthesizes new high entropy oxides based on the high entropy concept as thermistor materials to improve the structural stability of thermistor ceramic materials. Summary of the invention

[0004] The purpose of the present invention is to provide a thermistor material based on the concept of high entropy and a preparation method thereof, so as to improve the structural stability of thermistor ceramic materials. The present invention adopts the composition design concept of "high entropy alloy" to obtain a thermistor material with a significant negative temperature coefficient in the range of 0℃ to 100℃: (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4, and the material constant is B25℃ / 50℃ =4213K~4837K, temperature 25℃, resistivity is 4.23×10 5 Ω.cm~5.45×10 5 Ω.cm, and its entropy value is calculated to reach 2.08R, which is expected to be used to manufacture thermistors with excellent stability (0℃~100℃); at the same time, the thermistor material is prepared by the preparation method of transition metal oxide thermistor ceramics, and the prepared thermistor material has stable performance and good consistency.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A thermistor material based on the concept of high entropy, characterized in that the chemical expression of the thermistor material is: (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4, the thermistor material is used as a sensitive body in thermistors.

[0007] Furthermore, the method for preparing thermistor material based on the high entropy concept is characterized by comprising the following steps:

[0008] Step 1, weighing raw materials: magnesium oxide, cobalt trioxide, iron trioxide, chromium trioxide and zinc oxide in equal molar proportions, mixing the raw materials and then wet-milling them; after the ball milling, drying and grinding the slurry to obtain a precursor powder;

[0009] Step 2: calcine the precursor powder at 800°C-1000°C for 2-4 hours, and then perform secondary wet ball milling on the obtained powder; after the ball milling, dry and grind the slurry to obtain (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 powder;

[0010] Step 3: 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 powder is pressed into blocks, and the blocks are then cold isostatically pressed; finally, they are sintered at 1200℃-1300℃ for 4-8 hours to obtain the thermosensitive ceramic material.

[0011] Furthermore, wet ball milling is specifically as follows: a planetary ball mill is used, deionized water and anhydrous ethanol are used as solvents, and agate beads are used as ball milling media for wet ball milling, wherein the mass ratio of the raw material to the solvent is 1:1.5, the volume ratio of deionized water to anhydrous ethanol in the solvent is 1:1, and the ball milling time is 12 hours.

[0012] Furthermore, the drying temperature is 85° C. and the drying time is 24 hours.

[0013] Furthermore, the briquetting pressure is 15-25Kg / cm 2 , time is 1-4 minutes.

[0014] Furthermore, the cold isostatic pressing is specifically: maintaining the pressure at a pressure of 200-300 MPa for 1-3 minutes.

[0015] Furthermore, the thermistor material based on the high entropy concept is used in a thermistor. The front and back sides of the thermistor material are coated with silver paste electrodes respectively, and then annealed at 850° C. for 30 minutes to form a thermistor.

[0016] Based on the above technical solution, the beneficial effects of the present invention are:

[0017] The present invention provides a thermistor material based on the concept of high entropy. The starting point is to improve the structural stability of thermistor ceramic materials, and the composition design concept of "high entropy alloy" is applied to the thermistor material to obtain the thermistor material: (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4, where the special electronic structure of Mg and Zn atoms makes the thermistor material have an obvious negative temperature coefficient characteristic in the temperature range of 0℃~100℃, and the entropy value of the material reaches 2.08R, and the material constant is B 25℃ / 50℃ =4213K~4837K, temperature 25℃, resistivity is 4.23×10 5 Ω.cm~5.45×10 5 Ω.cm, which is very suitable as a sensitive body of a thermistor. In addition, the thermistor material is prepared by a preparation method of a transition metal oxide thermistor ceramic, the preparation process is simple, and the prepared thermistor material has stable performance and good consistency.

[0018] In summary, the present invention provides a thermistor material with excellent performance, stable performance and good consistency in the temperature range of 0°C to 100°C based on the concept of high entropy, which is suitable for manufacturing thermistors with excellent stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The thermistor material (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4's X-ray diffraction pattern.

[0020] Figure 2 The figure is a resistance-temperature characteristic curve diagram of the thermistor provided by the present invention. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and beneficial effects of the present invention more clearly understood, the present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0022] Example 1

[0023] This embodiment provides a thermistor material based on the concept of high entropy, and its chemical expression is: (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4, prepared by the following steps:

[0024] Step 1, weigh the raw materials: magnesium oxide, cobalt trioxide, iron trioxide, chromium trioxide and zinc oxide in equal molar proportions, mix the raw materials and put them into a planetary ball mill for wet ball milling; after the ball milling, dry the obtained slurry in an oven at 85°C, and grind to obtain (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 precursor powder; wherein the wet ball milling is specifically: wet ball milling is performed using deionized water and anhydrous ethanol as solvents and agate beads as ball milling media, wherein the mass ratio of the raw material to the solvent is 1:1.5, the volume ratio of deionized water to anhydrous ethanol in the solvent is 1:1, and the ball milling time is 12 hours;

[0025] Step 2: calcine the precursor powder in step 1 at 800°C for 2 hours, and then perform secondary ball milling on the obtained powder; after the ball milling, dry and grind the slurry to obtain (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 powder; wherein the secondary ball milling adopts the same wet ball milling as step 1;

[0026] Step 3: Mix the composite powder in step 2 at 15Kg / cm 2The block was pressed into a block under a pressure of 100 MPa for 1 minute; the block was then cold isostatically pressed and kept under a pressure of 200 MPa for 1 minute; finally, the block was sintered at 1200°C for 4 hours to obtain a thermosensitive ceramic material;

[0027] Step 4: coating the ceramic material sintered in step 3 with silver paste electrodes on both sides, and then annealing at a temperature of 850° C. for 30 minutes to form a thermistor.

[0028] Finally, this embodiment obtains a temperature range of 0°C-100°C and a material constant of B 25℃ / 50℃ =4820K, temperature 25℃, resistivity is 4.99×10 5 Ω.cm thermistor material; and, after aging at a temperature of 125°C for 500 hours, the absolute value of the resistance deviation is 0.34%.

[0029] Example 2

[0030] This embodiment provides a thermistor material based on the concept of high entropy, and its chemical expression is: (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4, prepared by the following steps:

[0031] Step 1, weigh the raw materials: magnesium oxide, cobalt trioxide, iron trioxide, chromium trioxide and zinc oxide in equal molar proportions, mix the raw materials and put them into a planetary ball mill for wet ball milling; after the ball milling, dry the obtained slurry in an oven at 85°C, and grind to obtain (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 precursor powder;

[0032] Step 2: calcine the precursor powder in step 1 at 900°C for 2 hours, and then perform secondary ball milling on the obtained powder; after the ball milling, dry and grind the slurry to obtain (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 powder;

[0033] Step 3: Mix the composite powder in step 2 at 20Kg / cm 2 The block was pressed into a block under a pressure of 200 MPa for 2 minutes; the block was then cold isostatically pressed and kept under a pressure of 200 MPa for 3 minutes; finally, the block was sintered at 1225°C for 4 hours to obtain a thermosensitive ceramic material;

[0034] Step 4: coating the ceramic material sintered in step 3 with silver paste electrodes on both sides, and then annealing at a temperature of 850° C. for 30 minutes to form a thermistor.

[0035] Finally, this embodiment obtains a temperature range of 0°C-100°C and a material constant of B 25℃ / 50℃ =4575K, temperature 25℃, resistivity is 4.53×10 5 Ω.cm thermistor material; and, after aging at a temperature of 125°C for 500 hours, the absolute value of the resistance deviation is 0.34%.

[0036] Example 3

[0037] This embodiment provides a thermistor material based on the concept of high entropy, and its chemical expression is: (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4, prepared by the following steps:

[0038] Step 1, weigh the raw materials: magnesium oxide, cobalt trioxide, iron trioxide, chromium trioxide and zinc oxide in equal molar proportions, mix the raw materials and put them into a planetary ball mill for wet ball milling; after the ball milling, dry the obtained slurry in an oven at 85°C, and grind to obtain (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 precursor powder;

[0039] Step 2: calcine the precursor powder in step 1 at 1000°C for 2 hours, and then perform secondary ball milling on the obtained powder; after the ball milling, dry and grind the slurry to obtain (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 powder;

[0040] Step 3: Mix the composite powder in step 2 at 20Kg / cm 2 The block was pressed into a block under a pressure of 300 MPa for 3 minutes; the block was then cold isostatically pressed and kept under a pressure of 300 MPa for 3 minutes; finally, the block was sintered at 1250°C for 6 hours to obtain a thermosensitive ceramic material;

[0041] Step 4: coating the ceramic material sintered in step 3 with silver paste electrodes on both sides, and then annealing at a temperature of 850° C. for 30 minutes to form a thermistor.

[0042] Finally, this embodiment obtains a temperature range of 0°C-100°C and a material constant of B 25℃ / 50℃ =4213K, temperature 25℃, resistivity is 4.23×10 5 Ω.cm thermistor material; and, after aging at a temperature of 125°C for 500 hours, the absolute value of the resistance deviation is 0.28%.

[0043] More specifically, the thermistor material (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 X-ray diffraction pattern Figure 1 As shown in the figure, it can be seen that the thermistor material (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 is a single spinel structure without other impurities; the resistance-temperature characteristic curve of the thermistor is as shown in Figure 2 As shown in the figure, it can be seen that the thermistor material (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 has a typical negative temperature coefficient characteristic.

[0044] Example 4

[0045] This embodiment provides a thermistor material based on the concept of high entropy, and its chemical expression is: (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4, prepared by the following steps:

[0046] Step 1, weigh the raw materials: magnesium oxide, cobalt trioxide, iron trioxide, chromium trioxide and zinc oxide in equal molar proportions, mix the raw materials and put them into a planetary ball mill for wet ball milling; after the ball milling, dry the obtained slurry in an oven at 85°C, and grind to obtain (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 precursor powder;

[0047] Step 2: calcine the precursor powder in step 1 at 1000°C for 4 hours, and then perform a second ball milling on the obtained powder; after the ball milling is completed, dry and grind the slurry to obtain (Co0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 powder;

[0048] Step 3: Mix the composite powder in step 2 at 25Kg / cm 2 The block was pressed into a block under a pressure of 4 minutes; the block was then cold isostatically pressed and maintained at a pressure of 300 MPa for 2 minutes; finally, it was sintered at 1275°C for 6 hours to obtain a thermosensitive ceramic material;

[0049] Step 4: coating the ceramic material sintered in step 3 with silver paste electrodes on both sides, and then annealing at a temperature of 850° C. for 30 minutes to form a thermistor.

[0050] Finally, this embodiment obtains a temperature range of 0°C-100°C and a material constant of B 25℃ / 50℃ =4820K, temperature 25℃, resistivity is 4.75×10 5 Ω.cm thermistor material; and, after aging at a temperature of 125°C for 500 hours, the absolute value of the resistance deviation is 0.29%.

[0051] Example 5

[0052] This embodiment provides a thermistor material based on the concept of high entropy, and its chemical expression is: (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4, prepared by the following steps:

[0053] Step 1, weigh the raw materials: magnesium oxide, cobalt trioxide, iron trioxide, chromium trioxide and zinc oxide in equal molar proportions, mix the raw materials and put them into a planetary ball mill for wet ball milling; after the ball milling, dry the obtained slurry in an oven at 85°C, and grind to obtain (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 precursor powder;

[0054] Step 2: calcine the precursor powder in step 1 at 1000°C for 4 hours, and then perform a second ball milling on the obtained powder; after the ball milling is completed, dry and grind the slurry to obtain (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 powder;

[0055] Step 3: Mix the composite powder in step 2 at 25Kg / cm 2 The block was pressed into a block under a pressure of 4 minutes; the block was then cold isostatically pressed and maintained at a pressure of 300 MPa for 3 minutes; finally, it was sintered at 1300°C for 8 hours to obtain a thermosensitive ceramic material;

[0056] Step 4: coating the ceramic material sintered in step 3 with silver paste electrodes on both sides, and then annealing at a temperature of 850° C. for 30 minutes to form a thermistor.

[0057] Finally, this embodiment obtains a temperature range of 0°C-100°C and a material constant of B 25℃ / 50℃ =4837K, temperature 25℃, resistivity is 5.45×10 5 Ω.cm thermistor material; and, after aging at a temperature of 125°C for 500 hours, the absolute value of the resistance deviation is 0.77%.

[0058] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.

Claims

1. A thermistor material based on the concept of high entropy, characterized in that: The chemical expression of the thermistor material is: (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4, the thermistor material is used as a sensitive body in thermistors.

2. The method for preparing thermistor material based on the high entropy concept according to claim 1, characterized in that: The following steps are involved: Step 1, weighing raw materials: magnesium oxide, cobalt trioxide, iron trioxide, chromium trioxide and zinc oxide in equal molar proportions, mixing the raw materials and then wet-milling them; after the ball milling, drying and grinding the slurry to obtain a precursor powder; Step 2: calcine the precursor powder at 800°C-1000°C for 2-4 hours, and then perform secondary wet ball milling on the obtained powder; after the ball milling, dry and grind the slurry to obtain (Co 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 powder; Step 3: 0.2 Cr 0.2 Fe 0.2 Mg 0.2 Zn 0.2 )3O4 powder is pressed into blocks, and the blocks are then cold isostatically pressed; finally, they are sintered at 1200℃-1300℃ for 4-8 hours to obtain the thermosensitive ceramic material.

3. The method for preparing thermistor material based on the high entropy concept according to claim 2, characterized in that: The wet ball milling is specifically as follows: a planetary ball mill is used, deionized water and anhydrous ethanol are used as solvents, and agate beads are used as ball milling media for wet ball milling, wherein the mass ratio of the raw material to the solvent is 1:1.5, the volume ratio of deionized water to anhydrous ethanol in the solvent is 1:1, and the ball milling time is 12 hours.

4. The method for preparing thermistor material based on the high entropy concept according to claim 2, characterized in that: The drying temperature is 85°C and the drying time is 24 hours.

5. The method for preparing thermistor material based on the high entropy concept according to claim 2, characterized in that: The pressure of briquetting is 15~25Kg / cm 2 , time is 1 to 4 minutes.

6. The method for preparing thermistor material based on the high entropy concept according to claim 2, characterized in that: The cold isostatic pressing is specifically: maintaining the pressure at a pressure of 200 to 300 MPa for 1 to 3 minutes.

7. According to the application of the thermistor material based on the high entropy concept in thermistors as claimed in claim 1, silver paste electrodes are coated on both sides of the thermistor material, and then annealed at 850° C. for 30 minutes to form a thermistor.

Citation Information

Patent Citations

  • Preparation method of negative temperature coefficient bead thermistor

    CN109411171A

  • High-entropy NTC thermistor ceramic material and preparation method thereof

    CN112624740A